EVALUATION OF THYROID HORMONE STATUS IN CHRONIC RENAL FAILURE - DR. SMITA PADHY,; DR. K. AMBIKA DEVI, (International Journal of Pharma and Bio Sciences, 2014)
Chronic kidney disease is a worldwide public health problem and now recognized as a common condition that is associated with an increased risk of cardiovascular disease. The study was designed to assess the status of thyroid hormones which is of great value in determining the prognosis of patients in chronic renal failure.60 cases and 40 healthy subjects (controls) were included in the study after taking informed consent. In all these subjects serum concentration of urea, creatinine, freeT3, free T4 and TSH were measured. Serum level of urea, creatinine were significantly increased. There was significant reduction in serum free T3 and freeT4 in cases as compared to controls (p<0.0001). There was no significant increase in serum level of TSH in cases as compared to controls (p =0.1323). From this study it was observed that chronic renal failure is associated with low thyroid function which is a risk factor for cardiovascular disease.